Investigating the Impact of Event Experience on Satisfaction and Behavioural Intention of Music Event Audiences - Trihadi Pudiawan Erhan; Cendera Rizky Anugrah Bangun (Faculty of Economics and Business Udayana University, 2024)
Many music events, be it concerts or festivals, are being held worldwide, and Indonesia is one of them. Motivation to attend a music festival is an experience that is a balance between fun, self-reflection, and impact. Our objective is to investigate how event experience helps shape satisfaction and, in turn, leads to future behavioural intention. This study uses Partial Least Squares regression to investigate six hypotheses. A total of 206 individuals in Indonesia who attended concerts in the past six months were surveyed, with 150 valid responses, giving a 72.8% response rate. The result shows that event experiences that are escapism, entertainment, and esthetic factors positively affect consumer satisfaction among music festivals and concert attendees, with the exception of education. Furthermore, consumer satisfaction significantly increases the tendency to both recommend and revisit. Thus, this study shows that event organizers need to create a memorable experience to gain favourable behavioural intention. Keyword: behavioral intention; customer satisfaction; event experience; music event